APAKAH HANYA TINGKAT RELIGUITAS YANG MEMPENGARUHI MINAT WISATA RELIGI SUNAN GIRI - Rochdianingrum, Widhi Ariestianti; Palupi, Dian; Rahayu, Rika; Faisal, Muhammad (Jurnal Ilmiah Manajemen dan Bisnis (JIMBis), 2022)
Religious tourism is one of the popular types of tourism in Indonesia and has a considerable influence on the local economy. This religious tour always attracts many visitors throughout the year. The purpose of this research is to know what factors influence people's interest in doing religious tourism in Sunan Giri, Gresik Regency. Respondents in this study were visitors to the tomb of Sunan Giri, both in groups and independently. Analysis of the relationship between the independent variable and the dependent variable in this study using SPSS. From the results of the study, it was found that the level of education, income level, and type of work did not affect the interest of tourists in visiting the tomb of Sunan Giri. Based on the results of the study, it was found that the level of religiosity affects the interest of tourists in doing religious tourism. The more religious a person is, the greater the interest of a person in doing religious tourism. This condition is because when tourists visit places that are considered sacred and bring blessings, the more calm their heart and get positive energy for themselves. Tourists also feel that what is said in prayer will be more easily answered because praying in a place that is considered to bring blessings and goodness.